Planeación de los recursos hídricos con fines de riego, en el sistema La Era, utilizando los sistemas de información geografíca (sig) - Luna Chalán, Angel Arcecia (2017)
The present work was carried out in the “La Era” irrigation system, which is located at the south of El Tambo parish, at the south east of Catamayo canton. The irrigation system is formed by the San Agustín glen ´s micro watershed of water supply and by the irrigation zone. They hydrographically belong to the high watershed of the Catamayo River. The availability of water was estimated through empiric methods such as the rational method, the ecologic polynomial method and the curve number method. They were correlated with the flow calculated in the collection site through a hydraulic windlass. Water gauging was made 20 times during a period of six months (from October 2016 to march 2017). The ecologic polynomial method was which better adjusted to the geomorphologic conditions of the watershed and to the water gauging, which allowed to estimate an average of 280 1/s regarding to the flow, with the 75% of probability in the collection point according to the general duration curve. In order to obtain the cadaster of the irrigation system, the four sectorial meetings were referenced geographically and the owners who had rights in the irrigation system were identified. The water requirements for the crops were estimated in base on the crops pattern identified in the irrigation zone. The ETo was calculated using the CROPWAT 8.0 software, based on the climatic data (minimum temperature, maximum temperature ºC, relative humidity %, wind speed m/s and heliophany hours a day), using the Penman-Monteih method, to a statistical series of 23 years, with the support of La Argelia, Catamayo, Malacatos and Cariamanga Stations. The annual volume available for the microbasin water catchment is 12.4 hm3, while the water demand according to the pattern of crops identified and with an application efficiency of 50%, is 5.99 hm3. Although the volume available is greater than the volume demanded by crops, there is a deficit in the months of June, July, August and September. With the goal to plan irrigation, it was taken into account the month with highest hydric requirement. This result was transformed to continuous caudal per hectare, and according to the efficiency in conduction and application, it was obtained the characteristic flow for each cultivation. Additionally, the irrigation system was divided into 17 irrigation modules with two watering frequencies in order to establish the agricultural calendar. Keywords: irrigation system, windlass, irrigation zone, déficit, characteristic flow.